Abuse of Halal Certificate: Legal & Procedural Analysis - Naziree, Md Yusof; Nor Aida, Ab. Kadir (2017)
The issues of halal logo cover the aspects of slaughtering, storage, displa"v, preparatiou. hvgiene and sanitation. It includes fbod and non-food category where most of technical preparations are not tackled by local religious enforcement. The lack of procedut'es and lxanpower lead these problems rernain unchanged and it looks like the legal provision of abusing the halal logo is irrelevant. Fuftherrnore' it is more cornplicated since the Malalsian law already excludes tlre non-Muslims frorn being arrested whereas most of the food manufacturers and daily products are dominated by thern. Horvever. the roles from Muslim non-govenrment organizations (NGO) are still imporlant to strerrgthen the enforcement besides creating better social awareness on shariah compliance. This article will discuss tlre legal constraints, practical alternatives and the need of politicalrvill in order to overcorne this r'veaknesses.